Concrete ground floor slab construction / Muhammad Razif Dinnie Mohd Tarmizi - Mohd Tarmizi, Muhammad Razif Dinnie (Universiti Teknologi MARA, Perak, 2021)
Slabs are a basic component in a construction, no matter how many levels the building is, there must be a slab. This component is vital in the construction of a basement because it serves as a transition between the ground and the structure. Non-load-bearing basement floor slabs must be distinguished from so-called bottom floor slabs. The latter play an essential part in the building's statics. Therefore, this report will discuss about concrete ground floor slab construction. This report was conducted for the building of Two Storey Surau at La Cottage, Taman Putra Perdana, Puchong Selangor that owned by Surau La Cottage Management. The objective of this report is to analyze the construction of ground floor slab and how it carried out. It will focus on the whole process and progress of concrete ground floor slab construction. It also investigates the equipment and machinery utilized in ground floor slab construction, as well as the time spent on construction. Other than that, this report also will show what material that will be used on the construction also the exactly amount of material that required and pre -determined measurements according to the plan.